New species of Porroglossum (Orchidaceae: pleurothallidinae) from Ecuador - Merino, Gilberto (Universidad de Costa Rica, 2013)
Three new species of Porroglossum from Ecuador are described and illustrated. Porroglossum miguelangelii is compared to the Peruvian P. lycinum, from which it differs by the longer, narrower petals with margins that are not obtusely angled below the middle and the presence of stigmatic tooth-like processes. Porroglossum merinoi is distinctive in that it is the only species with densely pubescent sepals. Porroglossum porphyreum is similar to P. schramii, but differs in the sepals with a thickened tail abruptly inserted at their apex, the petals with teeth on both the upper and lower margin, and the labellum provided with a longer and broader basal callus.